1992
DOI: 10.1136/adc.67.4.496
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced allergic sensitisation related to parental smoking.

Abstract: The objective of this study was to assess the role of parental smoking in changes, after a four year interval , in the prevalence and severity of the atopic state in 166 preadolescent children. Allergy skin prick tests were related to parental smoking habits and their changes during this same interval.The total number of cigarettes smoked by parents decreased in 56 families while it increased in only 16. Boys had significantly more persistently positive skin tests and changed more frequently from negative to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 19 publications
2
52
1
2
Order By: Relevance
“…Studies in adult female apoE Ϫ/Ϫ mice have shown that atherogenesis is accelerated with ETS exposure; however, these animals were also fed a high-fat (21%) diet. 25 Other studies have shown that males appear to be more sensitive to the effects of certain CVD risk factors (cigarette smoke and hypercholesterolemia) than females, 5,26 perhaps because of differences in immune response and/or hormonal effects. Studies have also shown that male apoE Ϫ/Ϫ mice have significantly more lesions than females when fed cholesterol-rich diets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adult female apoE Ϫ/Ϫ mice have shown that atherogenesis is accelerated with ETS exposure; however, these animals were also fed a high-fat (21%) diet. 25 Other studies have shown that males appear to be more sensitive to the effects of certain CVD risk factors (cigarette smoke and hypercholesterolemia) than females, 5,26 perhaps because of differences in immune response and/or hormonal effects. Studies have also shown that male apoE Ϫ/Ϫ mice have significantly more lesions than females when fed cholesterol-rich diets.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution has been previously shown to be associated with allergic sensitization in epidemiologic studies (6). Furthermore, in animal experiments, exposure to sulfur dioxide and ozone significantly enhanced allergic sensitization to inhaled allergens (7)(8)(9), and environmental tobacco smoke, which contains FA in higher concentrations, has been shown to increase the sensitization rate in children (22,23) and in experimental animal studies (21).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, most of the epidemiologic research on early wheezing in childhood focused on maternal smoking in pregnancy, postnatal ETS, and other postnatal environmental insults [6][7][8][9][10][11][12][13][14][15][16][17][18]. There are scarce studies reporting on the wheezing phenotypes related to prenatal exposure.…”
Section: Discussionmentioning
confidence: 99%